Tribal Welfare and Development Schemes – Impact on the Scheduled Tribes of Sittheri Hills Dharmapuri District in Tamilnadu - N. , Sanjaigandhi; B. , Revathy (International Journal of Psychosocial Rehabilitation, 2020)
Most of the areas occupied by the tribes are remote and immature. There are countless constraints dependable for a minor pace of the tribal development process than desired. The tribals have been given many rights and concessions under different statutes of central as well as state governments, but they remain deprived of the benefits arising out of such constitutional provisions due to their unawareness and indifference in enforcing agencies. The tribal people are unaware of various developmental programs launched by the Government of India and States, therefore reluctant in their use. In spite of the labors made by the government, the reimbursements are not disbursed to the really deprived poor people. The basic difficulty is not of the shortage of income but that of misconduct. The multiplicity of the agencies that transport out these programs has compounded the difficulty. Many times, they are not able to organize their efforts or fail to follow up on the programs to a longer extent. Against this environment, the study reviews the impact of different developmental programs of the Central and State Governments on the Scheduled Tribes of Sittheri Hills Dharmapuri District in Tamil Nadu.